Nematodes and trematodes associated with terrestrial gastropods in Nottingham, England. (2nd November 2022) - Andrus, P. S.; Rae, R.; Wade, C. M.
Abstract: A parasitological survey of terrestrial slugs and snails was conducted at popular dog walking locations across the city of Nottingham, with the intensions of finding gastropods infected with parasites of medical (or veterinary) importance such as lungworm (metastrongyloid nematodes) and trematodes. A total of 800 gastropods were collected from 16 sites over a 225 km 2 area. The extracted nematodes and trematodes were identified by molecular barcoding. Of the 800 gastropods collected, 227 were infected (172 had nematode infections, 37 had trematode infections and 18 had both nematode and trematode infections). Of the nematode infected gastropods genotyped, seven species were identified, Agfa flexilis, Angiostoma gandavense, Angiostoma margaretae, Cosmocerca longicauda, Phasmarhabditis hermaphrodita, Phasmarhabditis neopapillosa and an unknown Cosmocercidae species. Of the trematode infected gastropods genotyped, four species were identified, Brachylaima arcuate, Brachylaima fuscata, Brachylaima mesostoma and an unknown Plagiorchioidea species. No lungworm species were found within the city of Nottingham. To our knowledge, this study represents the first survey of gastropod-associated nematodes and trematodes in the East midlands of the United Kingdom.